The healthcare costs of poor air quality in Ireland: A review of potential data sources and methods - Hoy, Aislinn; Moriarty, Frank; Nolan, Anne (ESRI, 2025)
Air pollution is a major risk factor for disease and premature mortality worldwide. In Ireland, fine particulate matter (PM2.5), which originates largely from burning solid fuel for heating, and nitrogen dioxide (NO2), derived from road transport, in particular from diesel engines, are the main contributing sources of poor air quality. In addition to the mortality and morbidity burden, air pollution also imposes a significant economic burden, in terms of healthcare costs, lost productivity, impact on agricultural crops and damage to buildings and infrastructure. In this report, we scope out the data and methods to estimate the healthcare costs of poor air quality in Ireland, focusing on three types of healthcare: emergency inpatient hospitalisations, general practitioner (GP) care and prescribed medicines dispensed in community pharmacies (community pharmacy services). As the available data in Ireland preclude a comprehensive analysis of the healthcare costs associated with poor air quality, the data and methodological approach used in this report provide a framework that can be used to inform future data collection and research studies on this issue.